2004
DOI: 10.1177/1473095204042315
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Building: Clarifications for the Critics

Abstract: Many critiques of consensus building have been uninformed about the nature of this practice or the theory on which it was built, though there is extensive literature on both. It is grounded in the theory and practice of interest-based negotiation and mediation. It is not grounded in Habermas’ concept of communicative rationality, though theorists have found useful illumination in his ideas. Claims are often made about pathologies of consensus building based on cases where the conditions for authentic dialogue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
298
0
12

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 357 publications
(336 citation statements)
references
References 22 publications
(22 reference statements)
3
298
0
12
Order By: Relevance
“…This framing is also based on extensive research, such as that cited above, which demonstrates that when the conditions for authentic dialogue are met, genuine learning takes place; trust and social capital can be built; the quality, understanding and acceptance of information can be increased; jointly developed objectives and solutions with joint gain can emerge; and innovative approaches to seemingly intractable problems can be developed (Innes & Booher, 1999b;Innes, 2004). Even when the conditions are not all met, social capital and trust begin to develop through inclusion, deliberation, social learning and co-operation (Bloomfield et al, 2001).…”
Section: A New Paradigm For Participationmentioning
confidence: 99%
“…This framing is also based on extensive research, such as that cited above, which demonstrates that when the conditions for authentic dialogue are met, genuine learning takes place; trust and social capital can be built; the quality, understanding and acceptance of information can be increased; jointly developed objectives and solutions with joint gain can emerge; and innovative approaches to seemingly intractable problems can be developed (Innes & Booher, 1999b;Innes, 2004). Even when the conditions are not all met, social capital and trust begin to develop through inclusion, deliberation, social learning and co-operation (Bloomfield et al, 2001).…”
Section: A New Paradigm For Participationmentioning
confidence: 99%
“…These include the following: public influence (Lauber and Knuth 1999;Petts 2001;Rowe and Frewer 2000;Butterfoss 2006), consensus (Bass et al 1995;Innes 2004), increased understanding (Petts 1995;Laurian 2009), improved quality of decision (Laurian 2009;Brown and Wei Chin 2013) and increased trust (Wang and Wan Wart 2007;Laurian 2009). Other effectiveness criteria are also identified in the literature, such as representativeness (Crosby et al 1986;Rowe and Frewer 2000), complete information exchange (Crosby et al 1986;Rowe and Frewer 2000), independence (Lauber and Knuth 1999;Rowe and Frewer 2000), transparency (Lauber and Knuth 1999;Drew et al 2004) and cost-effectiveness (Rowe and Frewer 2000;Involve 2005).…”
Section: The Concept Of Public Participation Effectivenessmentioning
confidence: 99%
“…Indeed previous research has shown that there are many positive outcomes of the process (Innes & Booher, 1999); sometimes the aim is to build a shared understanding within stakeholder groups or to provide a voice to groups that ordinarily have little power to enact change (Innes, 2004). However, as the majority of African wildlife populations are found outside protected areas (Caro, 2001;Krugmann, 2001;Western, Russell, & Cuthil, 2009), it is imperative for the future of wildlife conservation that landholders become actively engaged in biodiversity management.…”
Section: Is Participation the Holy Grail Of Conservation Interventions?mentioning
confidence: 99%